A kinetic model for delayed coking process of Iranian vacuum residues. (2nd October 2019) - Torabi Esfahani, Farshad; Ehsani, Mohammad Reza; Ivakpour, Javad
Abstract: A four-lump kinetic model was developed for delayed coking process of Iranian vacuum residues. The feedstock and products were considered as a unique and three separated lumps, respectively, in the model. The product lumps were included gas (C1 –C4 ), distillate (C5+ –500 °C), and coke (toluene insoluble and 500 °C+). The reactions performed in an atmospheric batch pilot plant reactor by selected feeds at three temperatures (420, 450, and 480 °C) and four residence times (10, 30, 50, and 120 min). Reactions were assumed in first order and based on Arrhenius reaction rates. Also, the kinetic model was validated by a similar feed at different conditions that showed suitable precision with experimental results.